Nepal : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
The rapid growth of the financial system presents a number of challenges to maintaining financial stability in Nepal. There has been a rapid growth of the banking sector over the last few years. State-owned institutions continue to dominate the banking system. Equity market capitalization has increased sharply while government debt markets remain underdeveloped. Despite a challenging macroeconomic environment, the financial performance of the banking system has improved. The rapid increase in credit growth in recent years suggests growing credit risk.